A seasonally forced ocean-atmosphere model for paleoclimate studies - Schmittner, Andreas; Stocker, Thomas F. (American Meteorological Society, 2001)
Seasonal forcing is applied to an idealized model of the ocean–atmosphere system by prescribing monthly values of solar insolation at the top of the atmosphere and wind stress at the ocean surface. In addition, meridional near-surface wind velocities are applied for the advection term in the parameterization of the atmospheric moisture transport. The simulated seasonal cycle is compared with observations and reanalysis climatologies. It is found that the model can reasonably well simulate the present-day seasonal cycle. Largest model errors are found in the performance of the hydrological cycle. The sensitivity of the thermohaline circulation is examined with respect to seasonal versus annual-mean forcing. It is shown that meridional overturning is increased (20%) if seasonal forcing is applied instead of annual-mean forcing. Both seasonality in wind stress and insolation forcing contribute to the increased overturning. Two stable equilibria, one with deep water formation in the North Atlantic and one without, exist irrespective of seasonal or annual-mean forcing. However, lower sensitivity of the thermohaline circulation to meltwater input into the North Atlantic results if seasonal forcing is applied. It is shown that a large part of this difference is due to an increased effective vertical heat diffusion in the seasonally forced model. Vertical mixing is enhanced by the wind-induced seasonality in meridional overturning. A quantitative estimate of the difference in effective vertical eddy diffusivities between the seasonally and the annually forced model versions is given.